Bind us apart : how enlightened Americans invented racial segregation - Guyatt, Nicholas, 1973- (Oxford University Press, 2016)
The study of USA's on-going failure to achieve true racial integration, Bind Us Apart shows how, from the Revolution through to the Civil War, white American anti-slavery reformers failed to forge a colour-blind society.